Einsatz der Videokonferenztechnologie bei grenzüberschreitenden Gerichtsverfahren - Fucik, Robert (LeXonomica, 2021)
Application of Videoconference Technology in Cross-border Litigation. Regulation (EC) No 1206/2001 on taking of evidence is crucial for direct taking of evidence by foreign courts. The judge who has to give judgement follows the proceeding of taking evidence based on the rules of his own national law and language, without the involvement of a court of another Member State, in which the evidence is taken. In the framework of the Regulation (EC) No 1206/2001 on taking of evidence the Austrian Law also makes the application of videoconference technologies possible. The following contribution deals with the legal regulation of videoconference technology and is pointing out first practical experiences in the field of use of the respective regulation. Uporaba videokonferenčne tehnologije v čezmejnih sodnih postopkih. Ključnega pomena za neposredno pridobivanje dokazov sodišča v tujini je Uredba (ES) št. 1206/2001 o pridobivanju dokazov. V dokaznem postopku se sodišče, pred katerim poteka postopek, načeloma ravna po svojem nacionalnem pravu ter izvaja postopek v svojem jeziku brez udeležbe sodišča druge države članice, v kateri se izvaja dokazovanje. V okviru Uredbe (ES) št. 1206/2001 o pridobivanju dokazov avstrijsko pravo omogoča uporabo videokonferenčne tehnologije v čezmejnih sodnih postopkih. Predmet tega prispevka je njihova ureditev in prve praktične izkušnje pri njihovi izvedbi v okviru zadevne uredbe.